Ecosystem risk assessment of Georgina gidgee woodlands in central Australia. (June 2015) - Wardle, Glenda M.; Greenville, Aaron C.; Frank, Anke S. K.; Tischler, Max; Emery, Nathan J.; Dickman, Chris R.
Abstract: Ecosystems across the world, and the biodiversity they support, are experiencing increasing anthropogenic pressure, and many will not persist without intervention. Given their complexity, the International Union for Conservation of Nature has adopted an international standard for ecosystem risk assessment that builds on the strengths of the species‐based Red List criteria. We applied this protocol to the relatively understudied Georgina gidgee woodland ecosystem, which has a patchy but widespread distribution in central Australia. To address the extensive knowledge gaps, we gathered data to provide the first description of the characteristic biota, distribution of dominant species and the processes that support the ecosystem. Criteria evaluated include historical, current and future declines in spatial distribution, the extent and area of occupancy, and disruptions to abiotic and biotic processes. Future declines in suitable habitat were based on key climatic variables of rainfall, temperature and soil substrate. We also quantified the uncertainty in bioclimatic models and scenarios as part of predicting degradation of the abiotic environment. Overall, we assessed the risk status of Georgina gidgee woodlands as vulnerable based on the degradation of abiotic and biotic processes. Bioclimatically suitable habitat was predicted to decline by at least 30% in eight scenarios over the period 2000 to 2050. Predicted declines in overall suitable habitat varied substantially across all scenarios (7–95%). Pressures from grazing, weed encroachment and altered fire regimes further threaten the ecosystem; therefore, vulnerable status was also recorded for future declines based on altered biotic processes. Accurate mapping and monitoring of the study ecosystem should receive priority to inform conservation decisions, and sustainable grazing practices encouraged. Our findings focus attention on other patchily distributed ecosystems that may also have escaped attention despite their contribution to supporting unique biodiversity and ecosystem services. It is timely that environmental monitoring and policy account for these natural assets.